(untitled) (Ameghiniana, 2014)
This is an exhaustive analysis of the palynomorph assemblages, organic-walled marine phytoplankton and miospores from the Tucunuco Group. This group includes the La Chilca and Los Espejos formations and is exposed in the Central Precordillera of San Juan. Four localities were included in this study, i.e., Río Jáchal, Río de las Chacritas, Cerro La Chilca and Quebrada Ancha. Previous data concerning several fossil groups, such as graptolites, conodonts and brachiopods, suggest a mainly Llandovery–Wenlock? age for the La Chilca Formation and a Wenlock to locally Lochkovian age for the Los Espejos Formation. Marine palynomorphs are predominant in the two formations in all the studied sections. Although terrestrial palynomorphs are the minor component, trilete spores are abundant, diverse and biostatigraphically relevant in the Los Espejos Formation. Correlations using marine palynomorph assemblages and miospore biozones recognized worldwide allow constraining the age of the two stratigraphic units. Based on marine phytoplankton, the middle–upper part of the La Chilca Formation is assigned to the Wenlock. In the Los Espejos Formation, palynomorph assemblages allow the recognition, from the base to the top, of the Wenlock with doubts, the Ludlow, and the Pridolí. The Lochkovian has been documented exclusively in the northern part of the basin. This confirms the presence of the Silurian/Devonian boundary in the upper part of the Los Espejos Formation. A north-south correlation panel of the studied sections is presented. Resumen. NUEVA PROPUESTA BIOESTRATIGRÁFICA PARA EL GRUPO TUCUNUCO (PALEOZOICO INFERIOR), PRECORDILLERA DE SAN JUAN, ARGENTINA, BASADA EN PALINOMORFOS MARINOS Y TERRESTRES. Se realizó un análisis exhaustivo de las asociaciones palinológicas (fitoplancton marino de pared orgánica y mioesporas) del Grupo Tucunuco, Precordillera Central de San Juan, registradas en las localidades de Río Jáchal, Río de las Chacritas, Cerro La Chilca y Quebrada Ancha. Las dataciones previas, provenientes de diversos grupos fósiles como graptolitos, conodontes y braquiópodos, sugieren una edad principalmente llandoveriana–wenlockiana? para la Formación La Chilca y wenlockiana, hasta localmente lochkoviana, para la Formación Los Espejos. Se destaca la predominancia de los palinomorfos marinos en ambas unidades y en todos los perfiles analizados. Si bien los palinomorfos terrestres constituyen el componente minoritario, en la Formación Los Espejos las esporas trilete son abundantes, diversas y estratigráficamente relevantes. A partir de la correlación con asociaciones de palinomorfos marinos y con biozonas de esporas reconocidas en distintas regiones del mundo, se ajustan las edades de ambas formaciones, presentándose un nuevo esquema estratigráfico. Se confirma la edad wenlockiana para la parte media–superior de la Formación La Chilca, en base a su contenido fitoplanctónico. En la Formación Los Espejos los palinomorfos permiten distinguir, de base a techo, depósitos posiblemente wenlockianos, ludlovianos, pridolianos y lochkovianos exclusivamente en el perfil más septentrional estudiado. Se confirma por lo tanto la presencia del límite Silúrico/Devónico en la parte superior de esta formación. Se propone un esquema de correlación norte-sur de los perfiles estratigráficos estudiados.